From top-down land use planning intelligence to bottom-up stakeholder engagement for smart cities - a case study: DECUMANUS service products. (2017) - Ludlow, David; Khan, Zaheer; Soomro, Kamran; Marconcini, Mattia; José, Roberto San; Malcorps, Philippe; Lemper, Maria; Perez, Juan Luis; Metz, Annekatrin
Intelligence delivered by earth observation (EO) satellites performs a vital role in supporting ICT enabled urban governance, and the creation of decision making tools delivering integrated urban planning. This paper reviews the DECUMANUS project experience, detailing the development of the EO derived tools, and evaluating the service products that facilitate the deployment of top-down expertise in land use planning. The central purpose of the paper is to assess the potential for use of these DECUMANUS high resolution EO images and data, also to support bottom-up participatory planning, promoting co-design. It is concluded: 1) EO derived images and associated data offer great opportunity to deliver top-down decision making tools, which combined with auxiliary data, including participatory sensing data, effectively support integrated urban planning; 2) EO derived images also offer substantial potential as communication tools, enabling citizens to make more informed and responsible choices and participate in co-designed urban planning.